Promoting physical activity in regional and remote cancer survivors (PPARCS) using wearables and health coaching: randomised controlled trial protocol. Issue 5 (24th May 2019) - Hardcastle, Sarah J; Hince, Dana; Jiménez-Castuera, Ruth; Boyle, Terry; Cavalheri, Vinicius; Makin, Greg; Tan, Patrick; Salfinger, Stuart; Tan, Jason; Mohan, Ganendra Raj; Levitt, Michael; Cohen, Paul A; et al.
Abstract : Introduction: Physically active cancer survivors have substantially less cancer recurrence and improved survival compared with those who are inactive. However, the majority of survivors (70%–90%) are not meeting the physical activity (PA) guidelines. There are also significant geographic inequalities in cancer survival with poorer survival rates for the third of Australians who live in non-metropolitan areas compared with those living in major cities. The primary objective of the trial is to increase moderate-to-vigorous PA (MVPA) among cancer survivors living in regional and remote Western Australia. Secondary objectives are to reduce sedentary behaviour and in conjunction with increased PA, improve quality of life (QoL) in non-metropolitan survivors. Tertiary objectives are to assess the effectiveness of the health action process approach (HAPA) model variables, on which the intervention is based, to predict change in MVPA. Methods and analysis: Eighty-six cancer survivors will be randomised into either the intervention or control group. Intervention group participants will receive a Fitbit and up to six telephone health-coaching sessions. MVPA (using Actigraph), QoL and psychological variables (based on the HAPA model via questionnaire) will be assessed at baseline, 12 weeks (end of intervention) and 24 weeks (end of follow-up). A general linear mixed model will be used to assess the effectiveness of the intervention. Ethics and dissemination: Ethics approval has been obtained from St John of God Hospital Subiaco (HREC/#1201). We plan to submit a manuscript of the results to a peer-reviewed journal. Results will be presented at conferences, community and consumer forums and hospital research conferences. Trial registration number: ACTRN12618001743257; pre-results, U1111-1222-5698